Diagnosis of subdural haematoma by computed axial tomography: use of xenon inhalation for contrast enhancement. - Zilkha, E (1978)
A subdural haematoma is described in which a definite computed tomographic (CT) scan diagnosis was made only after contrast enhancement had been achieved by the inhalation of xenon. The different types of enhancement obtained with iodide containing contrast media and with xenon are discussed. The use of xenon to obtain further information in conditions which are inadequately elucidated by conventional CT must be balanced against its anaesthetic effects and relatively high cost.